The Use of Learning Media as an Effort to Improve Student Learning Outcomes: Classroom Action Research at State Elementary School 64 Timur City, Gorontalo Regency - Djafar, Shindi Juliana (Journal of Indonesian Primary School, 2024)
Education is created to meet learning standards for the creation of a quality generation that can make the country advanced and create progress in the economic field. In fact, the learning process will not run well without the use of learning media. In this study on the influence of the use of learning media on learning outcomes, a classroom action research method was used with Analyzing activities in the form of cycle I and cycle II activities using quantitative description data collection techniques. With the object of research of elementary school 64 East City in the subject of analyzing the influence of the use of learning media on learning outcomes of social sciences with a research sample of class IV. The results of the pre-cycle activities were only around 41.25%. In cycle I, using learning media in the form of videos actually increased the learning outcomes of social sciences in class IV children by an average of 59.25%. In this cycle II improvement, it actually had an effect on student learning outcomes that increased more than the results obtained previously with results of 81.5%. the positive influence of the use of learning media on the learning outcomes of social sciences of class IV students is greater than the negative influence caused by the use of social science learning media in class IV, namely with a ratio of 70:30. In this case, teachers should use more learning media that can help the teaching and learning process for elementary school students.